Behavior Patterns of Generation Z Consumers In E-Commerce Shopping Activities In Bengkulu - Yeni Herlina; Lydia Putri; Tri Febrina Melinda (Penerbit Jurnal Indonesia, 2025)
This research examines the meaning and behavioral patterns of Generation Z consumers in online shopping activities on e-commerce platforms in Bengkulu. Online shopping is integral to Generation Z's daily activities. The research focuses on how Generation Z interprets online shopping activities and the behavioral patterns they form when making online shopping decisions using e-commerce platforms. In practice, online shopping is not understood as simply purchasing goods, but as a meaningful experience for individuals. Generation Z's perspectives on online shopping exhibit diverse patterns, change rapidly, and are influenced by many factors. Generation Z's shopping behavior does not emerge simply. Developments in digital technology, ease of access to information, and social interaction in the digital space have also shaped how Generation Z makes purchasing decisions. However, understanding how personal and social meanings play a role in shaping Generation Z's consumption patterns remains limited. This gap requires further study. The research framework draws on the Theory of Planned Behavior to understand the underlying considerations of Generation Z in making online purchasing decisions. This theory is used to understand how individual attitudes, social norms, and perceptions of the ease and barriers to using e-commerce platforms shape purchasing decisions. For Generation Z, purchasing decisions are not influenced by personal beliefs but by social influences, including the powerful role of peers and influencers. The research approach employed descriptive qualitative methods, using in-depth interviews and observations of digital activities. Qualitative methods were chosen to explore the meaning and patterns of online shopping behavior among Generation Z consumers. The data obtained were analyzed in stages by selecting information, organizing it systematically, and drawing meaningful conclusions from the research findings.